A Need Analysis in Learning English for Students of Midwifery Program Unipdu Jombang - Rohmat Hidayat (JoEMS (Journal of Education and Management Studies), 2020)
Needs analysis is compulsory for the academy to set or develop the English curriculum to reach a set of competencies needed by the students. Needs analysis is used to find specific needs for the students in the academy. English for Specific Purposes (ESP) has offered different point of view in teaching-learning English. It modifies the conventional teaching-learning which concerns memorizing the pattern or grammar and vocabulary of the language to the teaching-learning based on the learners’ needs. This study is aimed at the main purpose: finding out the students’ needs of students of Midwifery program of UNIPDU Jombang in learning English. The qualitative procedure is employed in this study. The model used for identifying students’ needs for designing ESP syllabus follows Yalden’s model known as Language Program Development with a bit modification. The result of the need survey showed that reading has the highest degree of students’ demand followed by speaking, writing, and listening. Related to ESP, it indicated that the contents of the course were totally needed by the students in order to fill the need for their future professional career. Finally, the finding of the research becomes a reference to form the syllabus design or development of worksheet for ESP. Keywords: Need Analysis, Syllabus Development; Midwifery Students.